Value of a QALY and VSI Estimated with the Chained Approach - Sara Olofsson; Ulf-G. Gerdtham; Lars Hultkrantz; Ulf Persson (Lund University, School of Economics and Management, Department of Economics, 2016)
The value of a Quality-Adjusted Life-Year (QALY) and the Value of a Statistical Injury (VSI) are important measures within health economics and transport economics. Several studies have therefore estimated people's WTP for these estimates, but most results show problems with scale insensitivity. The Chained Approach (CA) is a method developed to reduce this problem. The objective of this study was to estimate the value of a QALY and VSI in the context of non-fatal road traffic accidents using CA. Data was collected from a total of 800 individuals in the Swedish adult general population using two web-based questionnaires. The result showed evidence of scale sensitivity both within and between samples. The value of a QALY based on trimmed individual estimates where close to constant at exteuro300,000 irrespective of the type and size of the QALY gain. The study shows promising results for using the original CA to estimate the value of a QALY and VSI. It also supports the use of a constant value of a QALY, but at a higher level than what is currently applied by HTA's.
Keywords: D61; D80; I18; J17; 330; contingent valuation; chained approach; scale sensitivity; quality-adjusted life-years; willingness-to-pay